Design and Construction of a Led Two-Dice System. - Rukundo, Ivan (Kabale University, 2024)
Microcontrollers are used in games like the MCU Chess, Snake, Led Tetris, Spaceship simulators, Pin Ball Machines, Poke Ball, Ludo, and Monopoly, among other games. In the MCU chess game, the microcontroller plays chess with the user through the serial port. The microcontroller initializes the chess board in memory and lets the user make the first move and the game proceeds on. The purpose of this study was to design and construct an LED two-dice system using a pie 18f452 microcontroller.